PERCEIVED ACCESS TO FINANCE AND SOCIAL ENTREPRENEURSHIP INTENTIONS AMONG UNIVERSITY STUDENTS IN SINDH, PAKISTAN - Ghulam Rasool Lakhan, Bahadur Ali Soomro, Amanullah Channa, Siraj Ahmed Channa, Ghulam Mujtaba Khushk (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of this article is to investigate the role of perceived access to finance (PAF) and social entrepreneurship intentions (SEI) among university students in Sindh, Pakistan.The article is based on cross-sectional data,and eight universities were selected to encourage the students for taking part in a survey.Different techniqueswere applied a five-point Likert-like scale usedto recognize their agreement and disagreement with the statement.Further,the technique of multiple regression analysis (MRA) is used to examine the proposed hypotheses for a study.The findings of this study found a significant and positive impact of attitudes towards behavior (ATB), subjective norms (SNs), perceived behavioral control (PBCO), and PAF on SEI. The outcome of the study validates the mediatory effect of TPB theory in a developing context. The direct positive relationship between PAF and SEI in the presence of TPB would further enrich the depth of the entrepreneurship literature.Our results have proven that determinants of TPB have a protagonist role in developing EI in general and SEI in particular. Furthermore, our study found a significant and positive impact of PAF on SEI. In our context, there is a significant role of PAF in developing SEI. Therefore, government and policymakers would be benefited from the findings of the study in considering and designing smooth policies for the provision of easy access to finance.Further, our results would help students to evoke SE and help to find out the solutions to be more self-assured when initiating a social business. Finally, a mediatory and direct link of the study would contribute to the literature of entrepreneurship, particularly for developing contexts.